Universal Design for Learning (UDL) in adult learning spaces - Hernández Barahona, Yajaira (2023)
Universal Design for Learning (UDL) provides multiple ways for learning, thereby responding to the diversity and inclusion of thousands of students in different educational and academic training centers. This experience was carried out in the Guatemala Republic School of Costa Rica, where this design was put into practice, considering individual differences, contexts, learning pace, progress in academic performance, personal skill, and competencies. According to Pastor (2017) there is evidence of great concern from the international arena regarding the high levels of school failure, which is linked to social inequalities, which translate into exclusion processes for many citizens. Therefore, it is important to reflect that, from didactic planning, pedagogical mediation should be considered within the framework of Universal Design Learning, which provides, through its principles and guidelines, learning opportunities for students and breaks with the social inequality gap that exists. Moreover, it is important that pedagogical mediators offer various learning environments in which minors, young people, and adults construct meaningful learning based on their individual competencies and skills. UDL proposes various planning methods, where the teaching person must articulate Universal Design for Learning with pedagogical mediation, while responding to the principals of providing multiple forms of Engagement, Representation, and Action-Expression, which guide the consideration of individual differences and respond to inclusion.